V. An examination of women's professional visibility in cognitive psychology. (August 2016) - Vaid, Jyotsna; Geraci, Lisa
Mainstream psychological research has been characterized as androcentric in its construction of males as the norm. Does an androcentric bias also characterize the professional visibility of psychologists? We examined this issue for cognitive psychology, where the gender distribution in doctoral degrees has been roughly equal for several decades. Our investigation revealed that, across all indicators surveyed, male cognitive psychologists are more visible than their female counterparts: they are over-represented in professional society governance, as editors-in-chief of leading journals in the field, as Fellows in professional societies, and as recipients of prestigious senior level awards. Taken together, our findings indicate that a gender parity in doctoral degrees in cognitive psychology does not translate into a parity in professional visibility. We discuss a variety of potential reasons for the observed gender gap and suggest that, without attention to gendered structures of status and power, as noted by Shields, existing gender hierarchies may persist and be reproduced.